ANALYSIS OF RTRTO60K16 PKX YARN PRODUCTION PROCESS WITH OBJECTIVE MATRIX (OMAX) METHOD - Supriyadi, Edi; Junaedi, Junaedi; Oktaviani, Hanni (Universitas Muhammadiyah Jakarta, 2021)
Productivity improvement research conducted at PT. XYZ with the core problem of minimizing waste and shortening lead time with the Objective Matrix (OMAX) method. The total percentage of product damage from January to October 2019 was 28.42% and the largest percentage of damage occurred in May amounting to 1009.26 bales of production and 33.89 bales of product damage with product damage percentage of 3.36%. The lowest damage occurred in March where the damage percentage was 2.74% with the number of products as much as 945.24 bales and damage struck as much as 25.88 bales. The results of the application using the objective matrix (OMAX) method are obtained that the selected productivity criteria include: Ratio 1 (Utility working hours), Ratio 2 (Electricity energy consumption), Ratio 3 (Labor utility), and Ratio 4 (Defective product) have a red value which means performance is still below standard performance and has not reached the target.